Evaluasi Program Manajerial Kepala Sekolah Dasar dengan Menggunakan Model CIPP - Waldatun Thai Atun (Peneliti.net, 2021)
The aims of this study were to determine: (1) the effectiveness of the principal's program implementation in terms of the context component (X1) at SDN Ciwandan District; (2) the implementation of the principal's managerial program on the input component at SDN Ciwandan District; (3) the effectiveness of the implementation of the principal's managerial program in terms of the process component at SDN Ciwandan District: (4) the effectiveness of the implementation of the principal's managerial program in terms of the product component at SDN Ciwandan District; (5) the implementation of the principal's managerial program in terms of the context (X1), inputs, processes, and product components at SDN Ciwandan District; (6) obstacles that hinder the implementation of the principal's managerial program at the Banten Site STKIP using the CIPP evaluation method. Collecting data with a questionnaire filled out by 300 respondents. And the sample is chosen randomly. The results showed: The evaluation of the implementation of the principal's managerial program with the CIPP evaluation model was in the effective category.